Experimental and numerical study of a piano key side weir with oblique keys. (6th December 2019) - Karimi, Mahmoud; Jalili Ghazizadeh, Mohammadreza; Saneie, Mojtaba; Attari, Jalal
Abstract: Side weirs deflect the approaching flow to the side channel with a specific angle. Considering this angled flow, the oblique shape of side weirs would improve the flow discharge efficiency. In this paper, a Piano Key Side Weir (PKSW) with oblique keys is proposed. Sixteen PKSWs with different key angles were studied in the laboratory, as well as two PKSWs by using CFD modelling. Flow characteristics and discharge coefficients of the proposed side weirs were investigated. Results show that a PKSW with positive key angles can decrease the flow disturbance (a phenomenon usually occurs in symmetric PKSWs), which results in higher discharge coefficients especially in high Froude numbers ( F 1 > 0.35). Among the studied PKSWs with oblique keys, the best performance was achieved with a PKSW with 30° key angle. The findings of this study can be used for a better design of PKSWs.